Quantification of training and match-load distribution across a season in elite English Premier League soccer players. Issue 1 (2nd January 2020) - Kelly, David M.; Strudwick, Anthony J.; Atkinson, Greg; Drust, Barry; Gregson, Warren
ABSTRACT: Objective : To examine training and match loads undertaken by soccer players competing in the English Premier League. Methods : Using a retrospective design, external (GPS) and internal training loads (sessions ratings of perceived exertion [sRPE-TL]) were examined in 26 players across the competition phase of the 2012–2013 English Premier League season. Within-subject linear mixed-models estimated the mean effects (95% confidence interval [CI]) for load data across 6-week mesocycles and 1-week microcycles. Results : Daily sRPE-TL (95% CI range, 15 to 111 AU) and total distance (95% CI range, 179 to 949 AU) were higher during the early stages (mesocycle 1 and 2) of the competition period. Overall, high-speed activity was similar between mesocycles. Across the training week, load was greater on match day and lower pre match-day (G-1) vs. all other days, respectively ( p < 0.001). sRPE-TL ( 70–90 AU per day) and total distance ( 700–800 m per day) progressively declined over the 3 days before a match ( p < 0.001). High-speed distance was greater 3 days (G-3) before a game vs. G-1 (95% CI, 140 to 336 m) while very high-speed distance was greater on G-3 and G-2 than G-1 (95% CI range, 8 to 62 m; p < 0.001). Conclusion : Periodisation of in-season training load is mainly evident across the weekly microcycle reflecting the recovery and preparation for matches.